An Analysis of Job Satisfaction Among Teachers Working in Government Colleges in Bangladesh - Rahman, Shaikh Moksadur (Prabandhan: Indian Journal of Management, 2012)
Job satisfaction is the result of various attitudes an employee holds toward his/her or her job, towards related factors, and towards life in general. It increases productivity on the one hand, and reduces absenteeism and turn-over on the other. The purpose of this study is to measure and analyze the job satisfaction among teachers working in Government colleges in Bangladesh. The primary data was collected from one hundred and thirty two teachers from different government colleges in Comilla district, Bangladesh. One-way Analysis of Variance (ANOVA) and t-test were employed to analyze the data. The results indicate that there were significant differences in job satisfaction across age, sex, rank, years of experience, academic degree, and academic results. No significant differences were found with regard to publications. The results of this study might be useful for the concerned authorities to enhance the level of satisfaction of the teachers working in Government colleges by taking necessary actions.